2018
DOI: 10.2903/j.efsa.2018.5147
|View full text |Cite
|
Sign up to set email alerts
|

Use of EFSA Pesticide Residue Intake Model (EFSA PRIMo revision 3)

Abstract: Since 2007, the EFSA PRIMo (Pesticide Residue Intake Model), an Excel-based calculation spreadsheet, is the standard tool used at EU level to perform the dietary risk assessment for pesticide residues in the framework of setting and reviewing of maximum residue levels for pesticides under Regulation (EC) No 396/2005 and in the peer review of pesticides under Regulation (EU) No 1107/2009. The model was now updated with regard to food consumption data derived from some recent dietary food surveys. In addition, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
242
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 298 publications
(242 citation statements)
references
References 10 publications
0
242
0
Order By: Relevance
“…EFSA performed a dietary risk assessment using revision 3 of the EFSA PRIMo (EFSA, ). This exposure assessment model contains food consumption data for different sub‐groups of the EU population and allows the acute and chronic exposure assessment to be performed in accordance with the internationally agreed methodology for pesticide residues (FAO, ).…”
Section: Consumer Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…EFSA performed a dietary risk assessment using revision 3 of the EFSA PRIMo (EFSA, ). This exposure assessment model contains food consumption data for different sub‐groups of the EU population and allows the acute and chronic exposure assessment to be performed in accordance with the internationally agreed methodology for pesticide residues (FAO, ).…”
Section: Consumer Risk Assessmentmentioning
confidence: 99%
“…The short‐term exposure assessment focussed on the commodities assessed in the present MRL application and was performed in accordance with the internationally agreed methodology (EFSA, ). The calculations were based on the highest residue concentrations (HR values) derived from supervised field trials; the list of input values can be found in Appendix D.2.…”
Section: Consumer Risk Assessmentmentioning
confidence: 99%
“…The consumer risk assessment was performed with revision 3 of the EFSA Pesticide Residues Intake Model (PRIMo). This exposure assessment model contains the relevant European food consumption data for different subgroups of the EU population (EFSA, ).…”
Section: Consumer Risk Assessmentmentioning
confidence: 99%
“…The evaluation reports submitted by the EMS (United Kingdom, ,b) and the exposure calculations using revision 3.1 of the EFSA Pesticide Residues Intake Model (PRIMo) (EFSA, ) are considered as supporting documents to this reasoned opinion and, thus, are made publicly available as background documents to this reasoned opinion.…”
Section: Assessmentmentioning
confidence: 99%
“…EFSA performed a dietary risk assessment for the agreed residue definitions using revision 3.1 of the EFSA PRIMo (EFSA, , ). This exposure assessment model contains food consumption data for different subgroups of the EU population and allows the acute and chronic exposure assessment to be performed in accordance with the internationally agreed methodology for pesticide residues (FAO, ).…”
Section: Consumer Risk Assessmentmentioning
confidence: 99%